CYB5D2 IN BREAST CANCER - Peng, Jingyi (My University, 2021)
Breast cancer (BC) the second leading cause of cancer death in Canadian women.1 The disease is affected by numerous genes with more to be discovered. Our lab has recently published cytochrome b5 domain containing 2 (CYB5D2) as a candidate tumor suppressor in BC.2 My research further supports this concept. In a tetracycline inducible CYB5D2 lines previously constructed in HER2+ HCC1954 BC cells, induction of CYB5D2 inhibited cell proliferation. The inhibition can be partially recovered once induction pressure was removed; recovery level was associated with the length of CYB5D2 expression with longer CYB5D2 induction accompanied with reduced recovery ability. This in vitro inhibition is supported by in vivo evidence; in xenografts formed by HCC1954 Tet-CYB5D2 cells, induction of CYB5D2 via administration of doxycycline in drinking water significantly inhibited tumor growth. To examine the potential mechanisms underpinning CYB5D2-derived inhibition, I was able to co-immunoprecipitate (Co-Ip) CYB5D2 and PTEN (phosphatase and tensin homolog) following ectopic expression of both in 293T cells, indicating the formation of the CYB5D2-PTEN complex. This possibility is further supported by co-localization of both ectopic proteins in 293T cells detected by immunofluorescence analysis. Furthermore, in HCC1954 Tet-CYB5D2 cells, a complex containing CYB5D2 and endogenous PTEN was co-immunoprecipitated following induction of CYB5D2 expression. Collectively, evidence supports an association of CYB5D2 with PTEN. I further characterized this association. Binding of PTEN with CYB5D2 was determined in 293T cells using a set of CYB5D2 mutants, including ΔCYB5, ΔTM, D86G, R7P, R7G, and Q167K. Complexes containing PTEN and individual CYB5D2 mutants could be precipitated via either CYB5D2 or PTEN, but not both. While the situation was not ideal, evidence nonetheless indicates that these structural elements of CYB52 were not essential for its association with PTEN.